Pharmacological interventions on early functional gastrointestinal disorders. Issue 1 (December 2016) - Salvatore, Silvia; Barberi, Salvatore; Borrelli, Osvaldo; Castellazzi, Annamaria; Di Mauro, Dora; Di Mauro, Giuseppe; Doria, Mattia; Francavilla, Ruggiero; Landi, Massimo; Martelli, Alberto; Miniello, Vito; Simeone, Giovanni; et al.
Abstract Background Functional gastrointestinal disorders (FGIDs) are chronic or recurrent gastrointestinal symptoms without structural or biochemical abnormalities. FGIDs are multifactorial conditions with different pathophysiologic mechanisms including altered motility, visceral hyperalgesia, brain-gut disturbance, genetic, environmental and psychological factors. Although in most cases gastrointestinal symptoms are transient and with spontaneous resolution in infancy multiple dietary changes and pharmacological therapy are often started despite a lack of evidence-based data. Our aim was to update and critically review the current literature to assess the effects and the clinical appropriateness of drug treatment in early (occurring in infants and toddlers) FGIDs. Methods We systematically searched the Medline and GIMBE (Italian Group on Medicine Based on Evidence) databases, according to the methodology of the Critically Appraised Topics (CATs). We included reviews, clinical studies, and evidence-based guidelines reporting on pharmacological treatments. Systematic reviews and randomized controlled trials (RCTs) concerning pharmacologic therapies in children with early FGIDs were included, and data were extracted on participants, interventions, and outcomes. Results We found no evidence-based guidelines or systematic reviews about the utility of pharmacological therapy in functional regurgitation, infant colic and functional diarrhea. In case of regurgitation associated with marked distress, some evidences support a short trial with alginate when other non pharmacological approach failed (stepped-care approach). In constipated infants younger than 6 months of age Lactulose is recommended, whilst in older ages Polyethylene glycol (PEG) represents the first-line therapy both for fecal disimpaction and maintenance therapy of constipation. Conversely, no evidence supports the use of laxatives for dyschezia. Furthermore, we found no RCTs regarding the pharmacological treatment of cyclic vomiting syndrome, but retrospective studies showed a high percentage of clinical response using cyproheptadine, propanolol and pizotifen. Conclusion There is some evidence that a pharmacological intervention is necessary for rectal disimpaction in childhood constipation and that PEG is the first line therapy. In contrast, for the other early FGIDs there is a lack of well-designed high-quality RCTs and no evidence on the use of pharmacological therapy was found.